Storming and forming: A case study of education policy implementation - Katherine Caves; Maria Esther Oswald-Egg (ETH Zurich, KOF Swiss Economic Institute, 2020)
Implementing education policy is as important as the design of the policy itself when it comes to improving education systems. This study analyzes education policy implementation using the case study of a new law's implementation in Serbia and a framework of key implementation determinants. We use a mixed-method approach to test whether all of the dimensions identified in the framework are necessary for implementation progress, and find that the content dimension is a barrier, context and capacity are unclear, and commitment and clients-actors' engagement-are supporting dimensions. Therefore, it is not necessary for implementation progress that ever dimension and determinant be a supporting factor. We develop potential explanations for how determinants may relate to implementation progress, and identify pathways for future research.
hdl:20.500.11850/413208
Keywords: 330; Implementation; education policy implementation; vocational education and training; educationsystems